Measurement of sulfatides in the amniotic fluid supernatant: A useful tool in the prenatal diagnosis of metachromatic leukodystrophy. Issue 2 (19th January 2022) - Kubaski, Francyne; Herbst, Zackary M.; Burin, Maira Graeff; Michelin‐Tirelli, Kristiane; Trapp, Franciele B.; Gus, Rejane; Netto, Alice B. O.; Brusius‐Facchin, Ana Carolina; Leistner‐Segal, Sandra; Sanseverino, Maria Teresa; Souza, Carolina Moura Fischinger de; Wilke, Matheus V. M. B.; et al.
Abstract: Metachromatic leukodystrophy (MLD) is an autosomal recessive lysosomal disorder caused by deficiency of arylsulfatase A (ARSA), leading to an accumulation of sulfatides. Sulfatides have been quantified in urine, dried blood spots (DBS), and tissues of patients with MLD. Newborn screening (NBS) for MLD has already been proposed based on a two‐tier approach with the quantification of sulfatides in DBS followed by the quantification of ARSA by liquid chromatography–tandem mass spectrometry (LC–MS/MS). Prenatal screening for MLD is also crucial, and sulfatide quantification in amniotic fluid (AF) can aid diagnosis. The prenatal study was initiated due to a family history of MLD at 19 weeks of gestation. ARSA was quantified in cultured amniocytes. C16:0 sulfatide was quantified by LC‐MS/MS in the supernatant of AF. Molecular analysis of the ARSA gene was performed in cultured amniocytes. ARSA was deficient in fetal cells, and C16:0 sulfatides were significantly elevated in comparison to age‐matched controls (3‐fold higher). Genetic studies identified the c.465+1G>A variant in homozygosis in the ARSA gene. Our study shows that sulfatides can be quantified in the supernatant of AF of MLD fetuses, and it could potentially aid in a faster and more accurate diagnosis of MLD patients.